1995
DOI: 10.1016/s0741-5214(95)70115-x
|View full text |Cite
|
Sign up to set email alerts
|

Late complication of a Greenfield filter associating caudal migration and perforation of the abdominal aorta by a ruptured strut

Abstract: We report the case of a 67-year-old woman who was admitted for surgical removal of a Greenfield filter that had been inserted 7 years before because of recurrent deep vein thrombosis associated with pulmonary embolism. This complication appeared on a plain abdominal radiogram that showed a 7 cm distal migration of the filter, a 30-degree angulation, and rupture of a strut at the level of the hub. Computed tomography, aortography, and ascending cavography demonstrated that the inferior vena cava was perforated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…In addition to the cases presented here, there are numerous reports detailing IVC perforation with adjacent pericaval injury, including duodenal, lumbar body penetration, and aortic injury with mural thrombus. [2][3][4][5][6][7] However, complication of indwelling filter placement is not limited to injury of pericaval structures; there is risk of IVC thrombosis, approximately 5% with long-term indwelling filters. 8 The finding of filter struts outside the IVC wall is a common finding on CT with reported rates of IVC perforation from 25% to 86% on CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cases presented here, there are numerous reports detailing IVC perforation with adjacent pericaval injury, including duodenal, lumbar body penetration, and aortic injury with mural thrombus. [2][3][4][5][6][7] However, complication of indwelling filter placement is not limited to injury of pericaval structures; there is risk of IVC thrombosis, approximately 5% with long-term indwelling filters. 8 The finding of filter struts outside the IVC wall is a common finding on CT with reported rates of IVC perforation from 25% to 86% on CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The fracture and subsequent migration of its struts, though infrequent and largely asymptomatic, have been shown to lead to several life-threatening complications [13], including small-bowel volvulus [14,15], duodenal perforation [16], acute myocardial infarction [17], and perforation of the abdominal aorta [18]. Decousus et al [3] found that although IVC filters led to an initial reduction in the incidence of PE, they were associated with an increase in recurrent deep venous thrombosis in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…2 The placement of permanent fi lters in patients with transient indications demands caution because the initial benefi ts may be canceled out by longterm drawbacks, such as recurrent DVT or other complications (perforation, migration, structural fracture, etc.). [4][5][6][7][8] Temporary or retrievable IVC fi lters have therefore often been employed instead of permanent fi lters in order to prevent PTE for a short period. In this case, the temporary IVC fi lter was placed and consequently incorporated with a large quantity of thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IVC fi lters have also been reported to cause various complications in the early and late stages following placement. [1][2][3][4][5][6][7][8] In this article, we present a very rare case of a surgical removal of a temporary IVC fi lter, which was tilted 90° and incorporated with a large thrombus.…”
Section: Introductionmentioning
confidence: 99%